(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the surgical outcomes of fungating sarcomas. Methods: This descriptive study was conducted in Orthopaedics and Spine Unit Hayatabad Medical Complex Peshawar and Rehman Medical Institute Hayatabad Peshawar from 2nd January 2016 to 2nd December 2020.Patients of both gender and all ages with fungating sarcoma of bony or soft tissue origin meeting the inclusion criteria were included in this study and operated. Analysis of patient’s characteristics, tumour type, surgery, complications, recurrence and mortality was noted in each case. Results: We operated 16 patients of fungating sarcomas. The mean age was 30.5±17 years. All patients were male. Soft tissue sarcoma was present in 8(50%) and bony in 8(50%). Upper limb sarcoma was noted in 9(56.25%),lower limb in 6(37.5%) and neck in 1(6.25%) patient. Resection of soft tissue sarcomas followed by reconstruction was performed in 4( 8.69%) patients. Forequarter amputation was performed in 6(37.5%) cases, 3(18.75%) patients underwent hip disarticulation and 3(18.75%) patients had transfemoral amputations. Local complication was noted in 4(25%) patients with 3(18.75%) had wound dehiscence and 1(6.25%) had local recurrence at three months. Post surgery the mean survival time was 8 months and at 2 years follow up only 4(25%) patients were alive. Conclusion: Poor post operative prognosis and high mortality was noted for fungating sarcoma in our series. We however advise surgery for fungating sarcomas to alleviate symptoms and misery of these patients and improve their quality of life.